2020
DOI: 10.1111/liv.14383
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota compositional and functional fingerprint in patients with alcohol use disorder and alcohol‐associated liver disease

Abstract: Background & aims Alcohol use disorder (AUD) represents the most common cause of liver disease. The gut microbiota plays a critical role in the progression of alcohol‐related liver damage. Aim of this study was to characterize the gut microbial composition and function in AUD patients with alcohol‐associated liver disease (AALD). Methods This study included 36 AUD patients (14 with cirrhosis) who were active drinkers and an equal number of matched controls. Stool microbial composition, serum levels of lipopoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 53 publications
2
79
0
Order By: Relevance
“…27 Recently, Addolorato et al published their findings of significant Akkermansia reduction in patients with alcohol use disorder, irrespective of the degree of liver disease. 28 In line, Grander et al found a depletion of Akkermansia in fecal samples from alcoholic hepatitis patients and Akkermansia supplementation protected mice against liver injury in experimental alcoholic liver disease. 29 Our study suggests that the reduction in Akkermansia abundance is related to the degree of liver inflammation as seen on liver biopsy in patients with alcoholic hepatitis.…”
Section: Discussionmentioning
confidence: 92%
“…27 Recently, Addolorato et al published their findings of significant Akkermansia reduction in patients with alcohol use disorder, irrespective of the degree of liver disease. 28 In line, Grander et al found a depletion of Akkermansia in fecal samples from alcoholic hepatitis patients and Akkermansia supplementation protected mice against liver injury in experimental alcoholic liver disease. 29 Our study suggests that the reduction in Akkermansia abundance is related to the degree of liver inflammation as seen on liver biopsy in patients with alcoholic hepatitis.…”
Section: Discussionmentioning
confidence: 92%
“…The panel was designed based on previous studies in older adults and their involvement in pathways and processes relevant to PF&S pathophysiology (i.e., inflammation, amino acid metabolism, and mitochondrial dysfunction) (Calvani et al, 2018b(Calvani et al, , 2020aMarzetti et al, 2019;Picca et al, 2019aPicca et al, , 2020b. Twenty-seven inflammatory mediators including cytokines, chemokines, and growth factors were assayed using the Bio-Plex Pro TM Human Cytokine 27-plex Assay kit (#M500KCAF0Y, Bio-Rad Laboratories Inc., Hercules, CA, USA) on a Bio-Plex R System with Luminex xMAP R Technology (Bio-Rad Laboratories), as described elsewhere (Ponziani et al, 2018(Ponziani et al, , 2019Marzetti et al, 2019;Picca et al, 2019a;Addolorato et al, 2020). Serum levels of C-reactive protein (CRP), myeloperoxidase (MPO), fibroblast growth factor (FGF) 21, and brain-derived neurotrophic factor (BDNF) were measured by using commercially available kits on an ELLA TM automated immunoassay system (Bio-Techne, San Jose, CA, USA).…”
Section: Measurement Of Inflammatory Metabolic and Mitochondrial Mamentioning
confidence: 99%
“…18 Human studies generally focused on the role of the gutliver axis in severe alcoholic hepatitis and decompensated cirrhosis. [19][20][21][22][23] Little is known about the mechanisms operating at earlier stages of ALD and only two studies reported increased intestinal permeability (IP) in association with alterations of the fecal microbiota in less than 50% of AUD patients. 24,25 Liver disease was not assessed in these reports.…”
Section: Introductionmentioning
confidence: 99%